2016
DOI: 10.4088/jcp.15m10166
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical Response With Homocysteine Reduction During Therapy With Reduced B Vitamins in Patients With MDD Who Are Positive for <em>MTHFR</em> C677T or A1298C Polymorphism

Abstract: Objective: This study was designed to evaluate the efficacy and safety of reduced B vitamins as monotherapy in adults with major depressive disorder (MDD) who were also positive for at least 1 methylenetetrahydrofolate reductase (MTHFR) polymorphism associated with depression and further test the hypothesis that reduced (metabolized) B vitamins will lower homocysteine in a majority of clinically responding patients. Methods: 330 adult patients with MDD (DSM-5) and positive for either MTHFR C677T or A1298C poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 17 publications
(18 reference statements)
0
32
0
1
Order By: Relevance
“…High levels of homocysteine have been implicated in increasing oxidative stress, inhibiting methylation reactions, and increasing DNA damage (Kennedy, ). Reduction of homocysteine levels has been associated with improvements in mood (Mech & Farah, ) and cognitive function (Smith et al., ). Micronutrients also assist with the citric acid cycle and electron transport chain, acting as co‐enzymes in mitochondrial aerobic respiration and energy production (Kennedy, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of homocysteine have been implicated in increasing oxidative stress, inhibiting methylation reactions, and increasing DNA damage (Kennedy, ). Reduction of homocysteine levels has been associated with improvements in mood (Mech & Farah, ) and cognitive function (Smith et al., ). Micronutrients also assist with the citric acid cycle and electron transport chain, acting as co‐enzymes in mitochondrial aerobic respiration and energy production (Kennedy, ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the considerable human research has suggested that broad-spectrum micronutrient treatment approaches have been more beneficial for the improvement of mood and behaviour than single nutrient studies (for reviews see: (Kaplan, Crawford, Field, & Simpson, 2007;Popper, Kaplan, & Rucklidge, 2017;Rucklidge, Johnstone, & Kaplan, 2009;Rucklidge & Kaplan, 2013). There are now a number of double-blind randomized controlled trials (RCT) supporting the positive effect of broad-spectrum micronutrients for the treatment of symptoms associated with clinical conditions, including autism (Adams et al, 2011), ADHD (Rucklidge, Frampton, Gorman, & Boggis, 2014), conduct disorder (Schoenthaler & Bier, 2000) and depression (Mech & Farah, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…V itamins and minerals (micronutrients) given in combination may provide an alternative to medication for the treatment of mental health issues with a growing body of literature supporting their efficacy. 1,2 Indeed, providing nutrients in combination appears to show some clinical benefit based on randomized placebo controlled trials (RCTs) [3][4][5][6][7] ; however, there are little long-term data systematically investigating their safety. A study that has investigated safety within a mostly North American community setting showed a reassuring safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…A. Mech ΠΈ соавт. [29] продСмонстрировали прСимущСства ΠΌΠ΅Ρ‚ΠΈΠ»Ρ„ΠΎΠ»Π°Ρ‚Π° ΠΈ Π΄Ρ€ΡƒΠ³ΠΈΡ… Π±ΠΈΠΎΠ°ΠΊΡ‚ΠΈΠ²Π½Ρ‹Ρ… Π²ΠΈΡ‚Π°ΠΌΠΈΠ½ΠΎΠ² Π³Ρ€ΡƒΠΏΠΏΡ‹ Π’ Π² качСствС ΠΌΠΎΠ½ΠΎΡ‚Π΅Ρ€Π°ΠΏΠΈΠΈ Ρƒ ΠΏΠ°Ρ†ΠΈΠ΅Π½Ρ‚ΠΎΠ² с мутациями Π³Π΅Π½Π° MTHFR ΠΈ тяТСлым дСпрСссивным расстройством.…”
Section: Discussionunclassified